Microtremor HVSR Analysis for Characterizing Subsurface Conditions Associated with Ground Movement Susceptibility - Rahmania, Rahmania; Sastrawan, Febrian Dedi; Amsal , Setiadi; Arisalwadi, Meidi; Samosir, Harrys; Rasmid, Rasmid (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Ground movement frequently occurs in areas with complex geological settings, yet subsurface information required for hazard assessment remains limited, particularly in rapidly developing regions. This study investigated the potential of microtremor Horizontal-to-Vertical Spectral Ratio (HVSR) analysis to characterize near-surface conditions associated with ground movement susceptibility in North Balikpapan, Indonesia. Microtremor observations were conducted at 27 measurement stations and processed using Geopsy following the SESAME reliability criteria. Dominant frequency, amplification factor, and sediment thickness derived from HVSR analysis were integrated with Digital Elevation Model (DEM)-based topographic information to interpret subsurface variability. The results reveal pronounced spatial variations in subsurface characteristics across the study area. Thick unconsolidated sediment deposits associated with low dominant frequencies were predominantly identified in the central and southern regions, whereas thinner and relatively stiffer subsurface materials occurred mainly in the northeastern area. Although amplification levels were generally low to moderate, the combination of thick sediment deposits and moderate-to-steep slopes indicates conditions that may increase ground movement susceptibility. These findings demonstrate that integrating HVSR-derived parameters with topographic information provides a practical, non-invasive approach for subsurface characterization and offers valuable baseline information to support geohazard assessment and land-use planning in rapidly developing regions.